Symposium 6: Researching Social Conflict in Collaborative Groups - Picard, Janice M. (Proceedings of the International Conference on Networked Learning, 2006)
There is a substantial body of literature examining conflict in social settings (Bartos & Wehr, 2002; Isenhart & Spangle, 2000; Coser, 1956) but considerably less understanding of social conflict in settings which are mediated by communications and information technologies (Hobman, Bordia, Irmer & Chang 2002; Graham, 2002). Understandings of collaborative environments have been acquired largely through the use of archived course transcripts. This strategy, while important in furthering our knowledge of computer mediated settings and collaboration in general, provides one understanding of learners’ online worlds. Methodologically, it has privileged observable behaviors over informal, and ‘back-stage’ (Goffman, 1969) or private social behaviors and processes (Jones & Cawood, 1998). This may be problematic when researchers wish to study phenomena such as private conflicts. This paper discusses one perspective for the study of covert conflict processes. It is argued that such an approach holds promise in obtaining more complete understandings of the meanings and dynamics of conflict in instructional groups in technology mediated settings.